On French and British Freedoms Early Bloomsbury and the Brothels of Modernism - Christine Froula (Cahiers Victoriens et Edouardiens)
In On British Freedom (1923), Clive Bell argued that ‘Great Britain is one of the least free countries in the world’ in respect not to political freedom but to such everyday freedoms as ‘an ordinary Frenchman’ enjoys. Whereas the subject of Bell’s freedom is male, for the Stephen sisters the differences within, as well as between, French and English law and culture intersected with their personal histories to give 46 Gordon Square a meaning it could never have had ‘had not 22 Hyde Park Gate preceded it.’ Against the usual view that the Stephens moved from ‘respectable’ Kensington to ‘disreputable’ Bloomsbury, the documents of early Bloomsbury show that the Stephen sisters escaped a Kensington house not entirely unlike a brothel for the Bloomsbury home where Virginia first had the ‘room with a lock on the door’ that she later makes the condition of a woman’s freedom. There Vanessa and Virginia, adventurers and revolutionaries, entered into the critical and creative dialogue with ‘French’ and ‘British’ freedoms that shaped their lives, their modern arts, and early Bloomsbury.